Web Based Assessment Alternative for Arabic Online Exam - Nur Fuadi Rahman; Ahmad Dakhoir; Ahmad Makki Hasan; Humairo Nur Ihsani; Nurul Khair (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
This study to explore the steps of web-based assessment using gnomio.com as a mean of evaluation during online Arabic language Course. This work uses a descriptive qualitative approach. As many as 56 college students of IAIN Palangka Raya were the subject of this work. The data collected for this work was obtained through direct observation, open response questionnaires, and interviews. The result of this work shows that the utilization of web-based assessment using gnomio.com on those students is well accepted in terms of perceived ease of use and perceived usefulness. The mobility indicator on perceived ease of use bolsters along with the pandemic situation. In terms of the Perceived usefulness of Web based assessment using gnomio.com, it gives feedback to the students compared to other applications.